2020
DOI: 10.1111/aphw.12226
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Mental Health during the COVID‐19 Pandemic: Moderator Role of Disaster Stressor and Mediator Role of Negative Affect

Abstract: Background Informed by the differential susceptibility to media effects model (DSMM), the current study aims to investigate associations of COVID‐19‐related social media use with mental health outcomes and to uncover potential mechanisms underlying the links. Methods A sample of 512 (62.5% women; M age = 22.12 years, SD = 2.47) Chinese college students participated in this study from 24 March to 1 Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
190
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(221 citation statements)
references
References 57 publications
(75 reference statements)
17
190
1
13
Order By: Relevance
“…In this context, it is worth mentioning the process of upward social comparison, which can be triggered by comparing the number of "Likes" with others or by comparing life styles (Vogel et al, 2014). Taken together, these findings may provide useful information with potential clinical implications about the way individuals use social media in the context of the coronavirus (COVID-19) pandemic as recent studies have reported that increased exposure to disaster-related information on social media may trigger negative affect, which can elicit mental health disorders (Zhao and Zhou, 2020), a contention that is aligned with the findings obtained since negative affect was a strong predictor of PSMU.…”
Section: Discussionmentioning
confidence: 84%
“…In this context, it is worth mentioning the process of upward social comparison, which can be triggered by comparing the number of "Likes" with others or by comparing life styles (Vogel et al, 2014). Taken together, these findings may provide useful information with potential clinical implications about the way individuals use social media in the context of the coronavirus (COVID-19) pandemic as recent studies have reported that increased exposure to disaster-related information on social media may trigger negative affect, which can elicit mental health disorders (Zhao and Zhou, 2020), a contention that is aligned with the findings obtained since negative affect was a strong predictor of PSMU.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, among all participants, frequent social media use similarly related to negative mental health. Indeed, several recent reports link social media use to poorer mental health during the COVID-19 pandemic ( 9 , 54 , 55 ). The relationship between frequent, or excessive, social media use and poor mental health has been shown prior to the pandemic ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the sample also reported limiting their exposure to traditional and social media as a way to cope. This may be an effective strategy based on historical findings of associations between adverse mental health consequences and repeated exposure to media after tragic events such as the 9/11 terrorist attacks (Otto et al, 2007 ) and the 2013 Boston Marathon bombing (Holman et al, 2014 ), as well as recent data linking increased social media use with increased depression during the COVID-19 pandemic (Holingue et al, 2020 ; Sun et al, 2021 ; Zhao & Zhou, 2020 ). In sum, the fact that the overwhelming majority of respondents reported engaging in adaptive and effective coping strategies is encouraging and suggests both awareness and practice of multiple empirically supported behavioral approaches for managing stress (e.g., Posluns & Gall, 2020 ).…”
Section: Discussionmentioning
confidence: 99%